Percepções de enfermeiros docentes sobre a interface saúde e meio ambiente na formação profissional - Peres, Roger Rodrigues (2014)
Introduction: The environmental quality and, consequently, population health has been the subject of constant concern of the different sectors of society in the past few years. In this aspect, when designed the interface health and the environment, it is essential that nurses take a position in the discussion. Given the above, one wonders what is the perception of nursing teachers of federal higher education institutions of Rio Grande do Sul on the approach to health and environment interface in professional nursing training? Aim: know the perception of nursing teachers of Rio Grande do Sul federal institutions of higher education about the approach to health and environment interface in professional nursing education. Method: qualitative study, with exploratory and descriptive type. Had the procedures of data collection, documentary research and semi-structured interview. Data were collected in the months from January to April 2013, in the Federal Institutions of Higher Education of Rio Grande do Sul. The study subjects were nurses teachers from selected institutions. The process of analysis of the findings was guided through the of referential content analysis. Results: The research revealed different perceptions about the studied subject, which are presented in three articles. The article "Teaching nurses relation to contemporary environmental problem" deals with different conceptions of the environment presented by the teachers' perceptions of current environmental issues and environmentally responsible actions which are carried out by them. The perception of health and environment interface is presented in the manuscript "The relationship between health and the environment in vocational training in nursing: perceptions of faculty nurses", which also show the approach that the subjects had the subject in their training and how they perceive that the current vocational training. Finally, the third article, "Environmental education in professional nursing education," portrays the subject concepts of environmental education, is adding even how they perceive environmental education in professional nursing education. Considerations: The study revealed that environmental perspective, inserted in this health and the environment and environmental education relationship, is still incipient in professional nursing education, a lot of because the very feeling of unpreparedness that subjects reported, the disciplinary fragmentation and poor communication between teachers on the subject. It is hoped that this study assists in the search for new ways of thinking about the environment and introduce the theme in nursing education, instigating, while conducting further research on the topic. Descriptors: Nursing. Education Higher. Environmental health. Environmental Education